Correlation between Non-Alcoholic Fatty Liver Disease (NAFLD) fibrosis score (NFS) with Left Ventricular Mass Index (LVMI) in patients with NAFLD - Tri Ferry Rachmatullah; Cecilia Oktaria Permatadewi; Hesti Triwahyu Hutami; Charles Limantoro; Hery Djagat Purnomo, MD, PhD (Faculty of Medicine, Diponegoro University, 2021)
Background: Cardiovascular-related mortality is a major concern in NAFLD. Advanced fibrosis was known to be associated with cardiovascular diseases. NAFLD Fibrosis Score (NFS) is used to identify the development of liver fibrosis in NAFLD patients. Left ventricular mass index (LVMI) is a sign of subclinical cardiovascular complications in NAFLD. The correlation between NAFLD fibrosis score with LVMI in NAFLD patients is not fully established.Objective: To analyze the correlation between NAFLD fibrosis score with LVMI in NAFLD patients.Methods: A cross-sectional study of NAFLD patients in Kariadi Hospital Indonesia. NFS was done using a formula based on clinical and biochemical parameters. LVMI was measured with echocardiography. Pearson’s, Mann-Whitney, and logistic regression were used for analysis.Results: A total of 64 patients with primary NAFLD were enrolled, 54.7% males and 45.3% females. Mean age was 52,8 ± 10,5 years (30-77 years). Based on NFS criteria, high probability group was the highest (50%), followed by intermediate probability group (34,4%) and low probability group (15,6%). Highest increase in LVMI was obtained in the high probability group (93,8%), followed by intermediate probability (59,1%), and low probability group (10%) respectively. There was significant correlation between NFS and LVMI (P 0,002). Logistic regression showed that NFS has a more significant correlation with LVMI compared to gender (P=0,002).Conclusion: NFS is a non‐invasive liver fibrosis scores which independently corelated with Left ventricular mass index (LVMI), a marker of cardiovascular abnormality.